2021
DOI: 10.1530/rep-21-0160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postovulatory oviduct changes and female stress on aging of mouse oocytes

Abstract: Postovulatory oocyte aging is one of the major causes for human early pregnancy loss and for decline in population of some mammalian species. Thus, the mechanisms for oocyte aging are worth exploring. While it is known that ovulated oocytes age within the oviduct and that female stresses impair embryo development by inducing apoptosis of oviductal cells, it is unknown whether the oviduct and/or female stress would affect postovulatory oocyte aging. By comparing aging characteristics including activation suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was inferred that the isthmus of yaks is also important for sperm transport, similar to other animals. Female parent-bound embryo development occurs by inducing apoptosis of oviductal cells ( 36 ), and a growth hormone regulates the apoptosis of oviduct cells and the expression of certain oviduct-specific proteins ( 37 ). Moreover, ceramide induces apoptosis in oviduct-derived primary cells via a caspase-3– and bcl-2–dependent pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was inferred that the isthmus of yaks is also important for sperm transport, similar to other animals. Female parent-bound embryo development occurs by inducing apoptosis of oviductal cells ( 36 ), and a growth hormone regulates the apoptosis of oviduct cells and the expression of certain oviduct-specific proteins ( 37 ). Moreover, ceramide induces apoptosis in oviduct-derived primary cells via a caspase-3– and bcl-2–dependent pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…What's more, it has been thought that apoptosis is a significant kind of cell death in oocyte loss. 25,26 Necroptosis is activated by pro-inflammatory signal transduction as well as ischemic injury and viral infection displaying Plasma membrane rupture and cell enlargement. The activation and assembly of necrosome complexes containing receptor-interacting serine/threonine protein kinase 1 (RIPK1) and RIPK3 will lead to phosphorylation and oligomerization of MLKL, which will then lead to lipid peroxidation, cation influx, and ultimately cell death.…”
Section: Ferroptosis and Its Activation Mechanismmentioning
confidence: 99%
“…However, the mechanisms underlying increased STAS levels in aging oocytes are largely unclear. Kong et al [11] and Chen et al [12] have reported that cytoplasmic calcium is correlated with STAS in aging mouse oocytes. Cui et al [13] observed that cytoplasmic Ca 2+ levels were increased in rat oocytes undergoing spontaneous activation during postovulatory aging.…”
Section: Introductionmentioning
confidence: 99%